The Effect of Leadership Style and Working Hours on Employee Morale - Patmawati, Patmawati; Arisinta, Octaviana; Ulum, Romiftahul (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
The purpose of this study is to determine how factors such as managerial style and length of working day affect morale at Salon Aviqa Rumah Cantik. The study used a quantitative approach, sampling 50 workers from the larger population of all those who work at Salon Aviqa Rumah Cantik. A questionnaire served as the method of information gathering. The research results suggest that the leadership style variable (X1) does not impact staff morale since both Ho and Ha accept it. tcount > ttable, or -0.290 > 2.011, and the sig value is 0.05 0.773. Therefore the conclusion holds. We may conclude that Ho is false since both the calculated tvalue (2.324 > 2.011) and the significance value (sig) of 0.05 are larger than the ttable and the significance threshold set at 0.005, respectively. Ha, the competing hypothesis is accepted. This demonstrates that employee morale is greatly affected by the variable Working Hours (X2). The data suggests that the Fcount value is higher (4.942) than the ftable value (3.20). This demonstrates, at the 0.05 significance level, that leadership style and working hours positively impact the observed variables. The preceding ftest findings suggest that the interaction between leadership style and working hours significantly affects the dependent variables at the 0.05 significance level.